IMPACT OF POPULATION ON THE KARST OF EAST SARAJEVO (BOSNIA AND HERZEGOVINA) - Mariana Lukić Tanović; Jelena Golijanin; Sanda Šušnjar (Zbornik Radova: Geografski institut "Jovan Cvijić", 2019)
Research of human settlements on the karst area of East Sarajevo starts with a brief overview of the City's characteristic traits and the influence of relief on the distribution of the population. The karst terrain was mapped using GIS tools, after which the percentage of the population and its concentration on the karst area of the East Sarajevo was determined. Karst areas have a low population density caused by difficult living conditions due to the vertical and horizontal dissection of relief, lack of mineral resources, geodynamic disasters, water shortages, specific climate conditions, degraded land, and vegetation. The consequences are the fragmentation of property, migration and aging of the population, lack of labor, weakening of the economy, etc. The research focus is to determine the degree of the anthropogenic impact on the karst environment and to apply the suitable methodology in the determination of the settlements categories according to the degree of karst environment vulnerability.